Perkembangan Iman Orang Muda Katolik di Perkotaan - Adelbred Sinaga; Antonius Denny Firmanto (Jurnal Penelitian Pendidikan Agama Katolik, 2023)
Young people are important assets of the country and the church. Young people are inseparable from efforts to achieve the goals of the nation and state as well as the church. They have new knowledge, a high level of creativity, uniqueness, and specificity that need to be developed. Thus, their presence can also bring blessings to others and development to the Church. Therefore, the role of young people should not be ignored. This research departs from the author's observation in his home parish. The author found a lack of activeness in the Catholic Youth in the parish. Young Catholics need assistance from the Church. Young Catholics who are the present and future of the Church need to be assisted and prepared from now on. This study aims to provide insight into the development of the Catholic Youth faith in the midst of technological developments (internet) and foster the interest of young Catholics in church life and participation in church services. This research uses quantitative methods to find out how active young people are in church activities, and also literature study methods. The author created questions in a google form and then distributed them to 103 respondents. The author also looks for references that match the author's ideas. What this writing aims to achieve is to know the level of activeness of Catholic Youth in church.